Evolocumab enables rapid LDL-C reduction and inflammatory modulation during in-hospital stage of acute coronary syndrome: A pilot study on Chinese patients - Ou, Ziwei; Yu, Zaixin; Liang, Benhui; Zhao, Lin; Li, Jianghua; Pang, Xinli; Liu, Qiyun; Xu, Cong; Dong, Shaohong; Sun, Xin; Li, Tangzhiming (Frontiers in Cardiovascular Medicine, 2022)
Background and aims: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has long been considered a key regulator in lipid metabolism. Its role as a potential player in immune response has recently earned much attention. However, the effects of evolocumab, an approved PCSK9 monoclonal antibody, on lipid reduction and inflammation regulation in Chinese patients with acute coronary syndrome (ACS) during their in-hospital stage after an index event are not well known. Methods: We conducted a case-crossover pilot study (http://www.clinicaltrials.gov/, NCT04730648) involving 31 patients hospitalized for ACS with elevated low-density lipoprotein cholesterol (LDL-C) level (≥70 mg/dL despite high-intensity statin) and 8 age- and gender-matched patients without coronary heart disease (CHD) as the baseline control. The patients with ACS received one dose of subcutaneous evolocumab (140 mg) on top of 10 mg/day rosuvastatin during hospitalization. Blood samples at baseline and 72 h post-evolocumab administration were collected for lipid and cytokine assessments. Results: The patients without CHD shared similar risk factors and LDL-C levels with the patients with ACS but exhibited a more activated inflammatory status. After single-dose in-hospital evolocumab, the median LDL-C level of patients with ACS decreased from 109.0 mg/dL to 41.4 mg/dL as early as 72 h, accompanied with reductions in other atherogenic lipids. Systemic inflammatory pattern was also altered, rendering a decrease in pro-inflammatory and anti-inflammatory cytokines. Conclusion: In this case-crossover study of the effect of PCSK9 antibody among Chinese patients, evolocumab on top of high-intensity statin during hospitalization led to a remarkable and rapid reduction in atherogenic lipids and an alteration in inflammatory status at early-stage post-ACS.